2021
DOI: 10.1088/2053-1591/abdb52
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical and tribological performance of Al-Fe-SiC-Zr hybrid composites produced through powder metallurgy process

Abstract: In this work a ternary Al-Fe-SiC metal matrix composites were reinforced using Zr particles through powder metallurgy process. The Al matrix and the reinforcements were mixed in high energy ball mill at a speed of 250 rpm over a period of 5 h so as to develop a homogenously dispersed composite material. The composite powders are then pressed at 500 MPa using hydraulic press. The compressed composite green compacts are then sintered at 500 °C for 2 h and allowed to cool under furnace atmosphere. The densities, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 31 publications
0
1
0
Order By: Relevance
“…The compressive strength of the Al-10Fe-10SiC-10Zr hybrid composites has increased with increase in SiC and Zr content and found to be around 205 MPa. The wear resistant properties also increased with increase in Zr Content [17].…”
Section: Introductionmentioning
confidence: 87%
See 1 more Smart Citation
“…The compressive strength of the Al-10Fe-10SiC-10Zr hybrid composites has increased with increase in SiC and Zr content and found to be around 205 MPa. The wear resistant properties also increased with increase in Zr Content [17].…”
Section: Introductionmentioning
confidence: 87%
“…From the image it is clear that there is oxide formation at the surface of the specimen. It is evident there is presence of MgO Al 2 O 3 and SiO 2 which helps in improving the wear resistance of the composites [17].…”
Section: Wear Analysismentioning
confidence: 98%
“…From the SEM images of MA6000 and X% Y 2 O 3 reinforced superalloys, it was understood that delamination type wear mechanism was dominant in the samples applied with 10 N load. Raghav et al [49] reported that deleminations were effective in the wear of Al-Fe-SiC-Zr composites. Amanov [50] reported that an oxide and debris area formed between the rubbing surfaces.…”
Section: Characterization Of Ma6000/x% Y 2 O 3 32 Alloy Materialsmentioning
confidence: 99%
“…In 2021, it was reported that 68 million tons of aluminium have been consumed globally, estimated to increase by 50% by 2030 [15]. Therefore, over the years, aluminium composites have been developed to improve their mechanical properties by using various fabrication methods [16] and processes [17] and types of reinforcements like ceramics [18], Rare Earths [19], recycled materials [20], non-metals [21], toxic wastes [22], etc. However, recycling aluminium chips has become a challenge in the current scenario.…”
Section: Introductionmentioning
confidence: 99%